How to Identify Students for School‐Based Depression Intervention: Can School Record Review Be Substituted for Universal Depression Screening?. Issue 1 (24th October 2012) - Kuo, Elena S.; Vander Stoep, Ann; Herting, Jerald R.; Grupp, Katherine; McCauley, Elizabeth
<x xml:space="preserve">Abstract</x> Problem Early identification and intervention are critical for reducing the adverse effects of depression on academic and occupational performance. Cost‐effective approaches are needed for identifying adolescents at high depression risk. This study evaluated the utility of school record review versus universal school‐based depression screening for determining eligibility for an indicated depression intervention program implemented in the middle school setting. Methods Algorithms derived from grades, attendance, suspensions, and basic demographic information were evaluated with regard to their ability to predict students' depression screening scores. Findings The school information‐based algorithms proved poor proxies for individual students' depression screening results. However, school records showed promise for identifying low, medium, and high‐yield subgroups on the basis of which efficient screening targeting decisions could be made. Conclusions Study results will help to guide school nurses who coordinate indicated depression intervention programs in school settings as they evaluate options of approaches for determining which students are eligible for participation.